Chemical profiling by LC-NMR of plants from Peruvian Amazonia with antiparasitic activities - Vasquez-Ocmin, P (2016)
Consejo Nacional de Ciencia y Tecnología (CONCYTEC) is acknowledged for PhD funding of Pedro Vásquez-Ocmín.